Treatment of a Traumatic Equine Wound Using Nile Tilapia (Oreochromis niloticus) Skin as a Xenograft - Costa, Behatriz Odebrecht; Lima Júnior, Edmar Maciel; Fechine, Francisco Vagnaldo; Nunes Alves, Ana Paula Negreiros; Oliveira de Melo, Miguel Marcos; Correia Ribeiro, Wesley Lyeverton; Pimentel Siqueira, Julliano; de Moraes Filho, Manoel Odorico (Acta Scientiae Veterinariae, 2020)
Background: Wounds are disruptions of the normal continuity of anatomic structures, generally due to local trauma. They are extremely prevalent in animals, especially horses, and a common reason for seeking veterinary attention. Their management aims to restore the function and integrity of the affected area in the shortest possible time and cost, while providing satisfactory cosmetic results. This task becomes challenging when working with horses, considering the contact between wounds and contaminated environment is common. Thus, the present study aims to report the case of a traumatic equine wound treated with Nile Tilapia Fish Skin (NTFS). Case: A male 27-year-old horse previously castrated, with no defined breed (NDB), and weighing 400 kg presented a 6.0 x 5.5 cm superficial wound in the distal left anterior limb (LAL) due to skin laceration. The animal belonged to the cavalry of the Military Police of Ceará, a public institution in Fortaleza, Brazil. Although in excellent general health, with no previous comorbidities or restriction of movement, the animal was removed from its role in equine-assisted therapy (EAT) until complete wound healing, aiming adequate evaluation of the novel biomaterial via lower influence of external factors. After informed consent from the owner was obtained, Nile Tilapia Fish Skin was applied to the lesion. The Ethics Committee on the use of animals of the Drug Research and Development Center of the Federal University of Ceará, Fortaleza, Brazil, approved the study protocol. Compliance with regulations on the ethical treatment of animals was performed. Nile Tilapia Fish Skin application followed a protocol similar to that established in human clinical studies. Initially, the horse was submitted to wound cleaning with tap water and 2% chlorhexidine gluconate, with no requirement of pre-treatment surgical debridement, as there was no area of necrosis. Before application, the biomaterial was washed thrice in sterile 0.9% saline for 5 min, allowing glycerol removal. Only one sample was required. Coverage of 1 cm of healthy skin in wound borders was performed to ensure movement in the first days of treatment or xenograft retraction after adherence to wound bed would not lead to uncovering of any affected area. The xenograft was then covered with a secondary dressing (i.e., dry gauze and regular bandage), followed by an elastic bandage, in order to reduce the risk of contamination and allow proper adherence. After seven days, when the secondary dressing was removed, it was observed the xenograft remained intact and well adhered to the wound bed. The patient’s distal LAL was washed with tap water and 2% chlorhexidine, and the xenograft was easily removed, exposing the wound bed. Clinical evaluation revealed remarkable improvement in the aspect of the lesion, with a decrease in the amount of granulation tissue and no significant presence of exudate. The above-cited findings motivated us to continue adopting the same protocol, which was repeated every seven days. On day 42 of treatment, after six applications of NTFS, wound reepithelialization was found to be complete, with no side effects detected on the animal, which successfully returned to its regular activities. Discussion: The current study demonstrates the potential of NTFS as a practical and low-cost dressing option for the management of accidental wounds in horses. The treated animal showed complete reepithelialization of the lesion, with satisfactory cosmetic and functional outcomes and no allergic reactions or toxicities. Also, no signs of discomfort (e.g., burning and itching) were detected, considering the patient did not try to remove the secondary dressing on its own and consistently respected the changing times.